Dinamika Psikologis Pada Remaja yang Melakukan Pernikahan Dini (Studi Kasus Di DP3AP2KB Unit PPA Kota Kediri) - Nila Ainu Ningrum; Uswatun Hasanah (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2026)
Early marriage is a complex social phenomenon that remains prevalent in Indonesia. In many cases, adolescent girls are the primary victims of this practice. This study aims to explore the psychological dynamics experienced by adolescents who engage in early marriage and identify the causal factors and impacts. This study used a descriptive qualitative approach, collecting data through in-depth interviews, observation, and documentation. The subjects were adolescents and their parents involved in early marriage cases handled by the DP3AP2KB PPA Unit in Kediri City. The results indicate that the main causal factors are premarital pregnancy, family pressure, local culture, and economic conditions. The psychological impacts experienced by adolescents include anxiety, stress, and mild depression due to unpreparedness for married life. This study contributes to the scientific understanding of adolescent psychological dynamics and the importance of preventive interventions from various parties.